Vulnerability of cross-country skiing to climate change in Finland – An interactive mapping tool. (October 2015) - Neuvonen, Marjo; Sievänen, Tuija; Fronzek, Stefan; Lahtinen, Ismo; Veijalainen, Noora; Carter, Timothy R.
Abstract: Cross-country skiing is one of the most popular recreational activities in Finland, but it is now becoming clear that it will be severely affected by climate change. In this paper we introduce an interactive vulnerability mapping tool that has been developed to raise awareness of the possible implications of climate change for cross-country skiing. Users of the tool are able to map indicators of exposure to climate change, characterising municipal-scale snow conditions under a warming climate, together with indicators of sensitivity and adaptive capacity, which are based on a national survey of 769 cross-country skiers aged 15–74 years from 2010. The indicators can be combined to produce composite vulnerability indices that can also be mapped. The mapping tool is designed to assist stakeholders in planning and developing skiing services and in studying the challenges of future regional cross-country skiing demand. It is available at:http://www.iav-mapping.net/U-C-IAV . Management implications: The U-C-IAV mapping tool can help to make the complexities of climate change impacts more recognisable, increase communication and awareness of climate change among decisions-makers and the general public and improve understanding of possible adaptation responses. The public sector still holds a key role in providing ski services for the population in Finland, and the tool could provide insights into the factors influencing vulnerability to climate change. This may assist stakeholders' decisions for designing strategies or developing policies to reduce vulnerability. The tool showcases cross-country skiers, representing an example of recreationists who already have experiences of adaptation to a changing climate and are expected to be affected even more in the future. As such, this study provides information that is potentially applicable or can serve as an example when investigating adaptation options for other winter activities in response to changing climate.